Time series analysis and forecasting intellectual methods using in epidemiology supervision system - Olga, Radivonenko; Tetiana, Korchak (Видавництво Національного університету «Львівська політехніка», 2009)
In this paper the problem of time series analysis is considered. The importance of a collaborative approach to the prevention and control of enteric infection are highlighted. Time series forecasting methods are described. Basic methods of statistical, regression and fractal analysis are used. Also the problem of epidemic thresholds modeling was considered. The implementation of the fuzzy clustering procedure in the method of epidemic thresholds calculation was proposed. This feature allows exclude epidemic information from the calculation data which will improve trueness and certainty of results substantially.
Keywords: R/s analysis; Hurst exponent; fuzzy clustering; epidemiology supervision